Rheological properties and sensory characteristics of green tea yogurt during storage - Amirdivani, S.; Baba, A.S. (2013)
Malaysian and Japanese green tea extract (2%) was added to a yogurt (MGTY and JGTY). Its dynamic rheological and sensory properties were evaluated and compared to those of a plain yogurt (PY) without the added green tea extract during 28 day storage at 4 °C. The plain yogurt exhibit a more compacted casein micelle aggregates network than that of green tea yogurts which was more runny and showed low viscosity attributed to the green tea extracts. The rheological analysis showed that the green tea yogurts had lower storage modulus modulus (G') and loss modulus (G'') values in the linear viscoelastic region than the plain yogurt. Sensory evalution showed that the green tea yogurts had significantly (p< 0.05) higher scored aroma and overall acceptability than plain yogurt. Incorporation of green tea extracts increased WHC in green tea yogurts contributed to lower synersi and higher total solid content than that plain yogurt during storage at 4 °C indicating both green tea yogurts may constitute a functional food with commercial application.